Estrategias didácticas lúdicas mediada por la WEB 2.0 para el fortalecimiento de la comprensión lectora en los estudiantes (2020)
The purpose of the research was to design a playful didactic strategy mediated by WEB 2.0 to strengthen students reading comprehension. It was structured under a quantitative approach, using an observation technique, collecting and characterizing the results with the use of descriptive statistics for data analysis, with the selection of a sample of 62 students belonging to the 5th grade of primary school of Teofilo Roberto Potes Education Institution located in Buenaventura, Valle del Cauca. To whom a pret-test and a survey were applied in order to in order to establish an initial parameter against habit, interest, frequency and level of reading competence and finally a post –test was applied to measure the dependent variable and the impact of the didactic strategy. As a result, the averages obtained by the students during the application of the post-test showed an increase in reading comprehension compared to the initial test. It is concluded from the research that by applying educational strategies mediated by WEB 2.0 contributes to the strengthening of reading comprehension in students.